Introduction to quantum dots - Jose, Rajan; Al-Douri, Yarub (Elsevier, 2022)
Quantum dots belong to a class of nanomaterials and are defined based on a fundamental length scale in materials, i.e., the exciton Bohr radius. Particles/clusters lower than the exciton Bohr radius are defined as quantum dots. In this chapter, the nanomaterials are defined based on the surface atoms and classification of nanomaterials based on morphologies are presented. The necessary theoretical framework is provided to define quantum dots based on the density of electronic energies. A protocol to determine the realistic materials structure is detailed. Properties of quantum dots such as size-dependent emission and size-dependent thermal properties are detailed. The surface effects of quantum dots on the charge transport through them is presented. Finally, the thermophysical properties of quantum dots are presented.